Paving the way to the integration of smart nanostructures. Part 1: nanotethering and nanowiring via material nanoengineering and electrochemical identification - LYONS, MICHAEL EDWARD (Electrochemical Science Group, 2009)
In this review essay some recent approaches to nanotethering and nanowiring of biomolecules such as redox enzymes and nanoparticles to solid surfaces to generate chemically modified electrodes to serve as platforms for bottom up designed nanostructures for use in nanobioelectronics are described.
PUBLISHED
Keywords: amperometric enzyme electrodes, electrochemical glucose detection, monolayer protected metal nanoparticles, carbon nanotube electrochemistry